(untitled) (Journal of International Studies, 2021)
The protracted humanitarian crisis in Rakhine state has forced millions of Rohingya to flee their homes from ethnic and religion persecution. Most headed to neighbouring countries including Malaysia, Bangladesh and Thailand by land or by sea across the Andaman Sea and Straits of Malacca. To date, nearly 1.2 million Rohingya live in Rohingya refugee camps in Cox’s Bazar since the mass exodus in 2017. As the world’s largest refugee influx, the Rohingya crisis has affected not only Myanmar but also the neighbouring countries and ASEAN member states. For the past 40 years, ASEAN member states in particular Malaysia and Thailand have been a preferred destination for refugees seeking refuge from violence and human rights abuse. In light of this, ASEAN has adopted security mechanism as part of regional responses for addressing the crisis facing the Rohingya ethnic. This article demonstrates, first, the mechanism and responses adopted by ASEAN in handling the influx of Rohingya refugees in Southeast Asia. Second, this article scrutinizes challenges to ASEAN’s efforts and way forward to resolve the burgeoning refugee issue. By exploring these collective efforts, this article investigates the extent to which these efforts and approaches play a functional role to suppress clandestine movement of Rohingya and subsequently protect the refugees. This article obtains its data from textual analysis including media reports, policy papers, academic articles, and official statements from ASEAN and ASEAN member states. The findings conclude that concerted efforts from ASEAN, albeit limited, are significant to providing new opportunities to strengthen national and regional protection for this vulnerable population.